Pengaruh Sosial Media Marketing dan Pengalaman Merek terhadap Niat Berkunjung Kembali, Kepercayaan Merek dan Loyalitas Merek pada Starbucks Indonesia - Lutfiah, Namira Ghassani; Astuti, Budi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The presence of social media today is able to create a wider marketing space for business actors, so it is important for business actors to maximize marketing effectiveness through social media. Based on the results of previous research, it was found that there was a gap in research results regarding the influence of social media marketing. Therefore, this research was conducted to prove the influence of social media marketing and brand experience on revisit intention, brand trust and brand loyalty at Starbucks. The population in this study were Yogyakarta residents who had visited Starbucks Indonesia. Sampling was carried out using the convenience sampling method with a total of 280 respondents. Data collection was carried out by distributing questionnaires. The SEM results show that there is a positive and significant influence between social media marketing and brand experience on revisit intention, brand trust and brand loyalty. These results have implications for marketers to develop marketing strategies related to social media marketing